Raman Spectra Studies of Inner "Anode | Electrolyte" Interface on ESC and ASC SOFCs. (10th July 2019) - Eliseeva, Galina; Agarkov, Dmitrii A; Burmistrov, Ilya; Gamova, Anastasiya; Ionov, Igor; Rabotkin, Sergey; Semenov, Vyacheslav; Solovyev, Andrey; Tartakovskii, Ilya; Bredikhin, Sergey I
Abstract : In this work we present the results of in-situ case studies of fuel oxidation at the SOFC anode for anode-supported cells with thin-film electrolyte deposited by magnetron sputtering technique in comparison with studies carried out on optically transparent single-crystal membrane based electrolyte-supported model SOFC. Changes of the valence state of Ce ions were studied under different current loads applied to the cell, these changes were indicated in the Raman spectra obtained from inner interface of electrolyte membrane and anode electrode. Area of the corresponding peak in Raman spectra of ceria was studied for different working conditions for both cells constructions. Special processing technique gave opportunity to obtain more relevant data.